Constitutional Struggle in Sri Lanka. (June 2022) - Gomez, Mario
Sri Lanka has alternated between authoritarian politics and constitutional democracy over the past 70 years. For 25 years after independence, the country functioned as a constitutional democracy with regular elections and power alternating between the two main political parties. Since 1972, political elites have used constitution-making as a method of consolidating their hold on political power. In 2015, the 19th Amendment to the Constitution trimmed the powers of the President and provided for a balanced form of power-sharing between executive and legislature. It enhanced the independence of the courts and the fourth-branch institutions. However, these gains were reversed by the 20th Amendment, passed in 2020. Against the backdrop of an intense competition for political power and the manipulation of constitutions to retain power, this contribution discusses three recurring sites of constitutional struggle and debate in Sri Lanka: struggles over presidentialism, power-sharing and the place of Buddhism in the constitution. This paper contends that a return to constitutional democracy will require, at a minimum, a revisitation of the first two issues, even if the third — the place of Buddhism — remains untouched. The paper concludes by arguing that while all three constitutional struggles have a different historical trajectory and different dynamics, they are all part of a larger struggle — the struggle to transform Sri Lanka from a Buddhist-majoritarian state into a plural, multi-ethnic and multi-religious society in law and in practice.